The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0238172
|View full text |Cite
|
Sign up to set email alerts
|

A simple predictive model for estimating relative e-cigarette toxic carbonyl levels

Abstract: E-cigarette devices are wide ranging, leading to significant differences in levels of toxic carbonyls in their respective aerosols. Power can be a useful method in predicting relative toxin concentrations within the same device, but does not correlate well to inter-device levels. Herein, we have developed a simple mathematical model utilizing parameters of an e-cigarette’s coil and wick in order to predict relative levels of e-liquid solvent degradation. Model 1, which is coil length/(wick surface area*wraps),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…Poor wicking efficiency may lead to a dry wick and overheated e-liquid (dry puff), which promotes the formation of carbonyls and other toxic compounds 2 , 10 , 13 , 15 . Coil location, orientation, resistance and wick material, as well as power output, have been shown to affect carbonyl generation significantly 13 , 15 , 86 . E-liquid physical properties are also important in carbonyl formation 15 , 47 , 84 , 86 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Poor wicking efficiency may lead to a dry wick and overheated e-liquid (dry puff), which promotes the formation of carbonyls and other toxic compounds 2 , 10 , 13 , 15 . Coil location, orientation, resistance and wick material, as well as power output, have been shown to affect carbonyl generation significantly 13 , 15 , 86 . E-liquid physical properties are also important in carbonyl formation 15 , 47 , 84 , 86 .…”
Section: Resultsmentioning
confidence: 99%
“…Flavourings may also contribute to the formation of carbonyls, as well as the characteristics of the e-cigarette devices, especially the applied voltage, coil resistance and wicking material [47][48][49]86,87 . Poor wicking efficiency may lead to a dry wick and overheated e-liquid (dry puff), which promotes the formation of carbonyls and other toxic compounds 2,10,13,15 . Coil location, orientation, resistance and wick material, as well as power output, have been shown to affect carbonyl generation significantly 13,15,86 .…”
Section: Polycyclic Aromatic Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Published research on both cannabis and nicotine vaporization products has demonstrated that higher concentrations of undesirable and potentially toxic thermal degradation products are produced as temperature (or device power output) increases [7,[27][28][29]. These thermal degradants include aromatics (e.g., benzene, styrene), carbonyl compounds (e.g., formaldehyde, methacrolein), and others (e.g., polyaromatic hydrocarbons, carbon monoxide) that should be avoided due to the potential for toxicity.…”
Section: Heating Coil Temperature and Implications For Consumer Riskmentioning
confidence: 99%